Complete genome sequence of potential plant growth-promoting Bacillus altitudinis strain AIMST-CREST03 isolated from paddy field bulk soil - Sivaprakasam, Sumitra; Mohd Azim Khan, Nur Arisa; Fan, Tan Yee; Kumarasan, Yukgehnaish; Sicheritz-Pontén, Thomas; Petersen, Bent; Mohd Hata, Erneeza; Vadamalai, Ganesan; Parimannan, Sivachandran; Rajandas, Heera (American Society for Microbiology, 2024)
We present the complete genome of a potential plant growth-promoting bacteria Bacillus altitudinis AIMST-CREST03 isolated from a high-yielding paddy plot. The genome is 3,669,202 bp in size with a GC content of 41%. Annotation predicted 3,327 coding sequences, including several genes required for plant growth promotion.